Kedudukan Kelompok Minoritas dalam Perspektif HaM dan Perlindungan Hukumnya Di Indonesia - Zul Fadhli, Yogi (Jurnal Konstitusi, 2014)
Minority group is a social entity which can not be denied its existence. The plural minority condition is defined as diversity of the majority on the basis of identity, religion, language, ethnicity, culture or gender. The number is usually not much when compared to the population in a country and be in a dominant position. Vulnerable minority groups become victims of human rights, therefore the legal protection given. In a human rights perspective, this group is at a level equivalent  to other individual rights holders and have special rights. Special rights are not privileges, but rights granted so the dignity of minority groups can be lifted.